Nexus of green human resource management and sustainable corporate performance: the mediating roles of green behavior and green commitment - Thanh Tiep Le; Duc Hieu Tham (Journal of Trade Science)
Purpose – The driving force behind this study is the need to learn more about the ways in which green human resource management (GHRM) can impact sustainable corporate performance (SCP), especially in the context of Ho Chi Minh City's manufacturing sector. The primary objective is to analyze the roles of GHRM, green behavior (GBH) and green commitment (GCM) in relation to SCP, as well as identify the mediating roles of green behavior and green commitment in the relationship between GHRM and SCP. Design/methodology/approach – The research design employs a quantitative approach to investigate the nexus of GHRM and SCP, with a focus on the manufacturing sector in Ho Chi Minh City. Methodologically, the study integrates the ability-motivation-opportunity (AMO) and resource-based view (RBV) frameworks to construct a comprehensive theoretical model. Data are gathered from a sample comprising 322 senior managers and directors representing various enterprises. Analysis is conducted utilizing Smart PLS software version 3.3.7, employing partial least squares structural equation modeling (PLS-SEM) to assess both first-level and second-level variables in a two-step process. Findings – The empirical findings underscore significant relationships between GHRM, green behavior, green commitment and SCP. Specifically, the study reveals that GHRM positively influences green behavior, green commitment and SCP. Additionally, both green behavior and green commitment exhibit positive effects on SCP. Furthermore, the research confirms the pivotal mediating roles of green behavior and green commitment in the relationship between GHRM and SCP. Originality/value – In terms of originality and value, this study makes notable contributions to both theoretical understanding and practical implications in the field of sustainable business management. By delving into the intricate interplay between GHRM, green behavior, green commitment and SCP, this research extends existing knowledge and offers novel insights. Moreover, the identification of the mediating roles of green behavior and green commitment enriches the theoretical frameworks in this domain. The findings provide practical implications for businesses, particularly in Ho Chi Minh City's manufacturing sector, by emphasizing the significance of optimizing human resource practices for achieving sustainable development goals. This research thus contributes to enhancing competitiveness and sustainability in similar industries, offering valuable guidance for strategic decision-making and policy formulation.